Suspected Allergic Reaction Among Hospitalized Patients: Narrative Review And Consensus Recommendation - Dr. Karan J. Yagnik; Miss. Aayushi Dave (Innovative Journal of Medical and Health Sciences, 2022)
Background: Patients with history of drug allergy pose socio-economic and medical concerns which may lead to deviations from standards of care. Accurate history taking fast and clear documentation for information transmission are important in, prevention of drug allergy administration. Types of allergy, food provided by hospital, hospital environment and internal / external drugs are main important allergic agents are also taken into count. Aim: Drug allergies are unpredictable immunologic adverse effects. Hyper-sensitivity about especially drug or other hung around patient. To analyze and to find serious cases are aim of the study. Our aim at the paper is to provide proper information and guide for anaesthesiologist and other nursing staff. Method: Consulting patients with drug allergy history. We find out lots of literature about allergy and inpatient treatment. This paper compares all the studies.